Fifth contribution to the knowledge of water mites (Acari: Hydrachnidia) from the Comoros: a checklist and description of one new genus and four new species - Pešić, Vladimir M.; Smit, Harry; Mary, Nathalie (Zootaxa, 2018)
New records of water mites (Acari: Hydrachnidia) from the Comoros are presented. One genus, i.e. Lagoenaxonopsalbia Pešić & Smit, and four species, i.e. Platymamersopsis mayottensis (Anisitsiellidae), Torrenticola mayottensis (Torrenticolidae), Lagoenaxonopsalbia comorosensis (Aturidae) and Djeboa davecooki (Mideopsidae) are described as new to science. Arrenurus comorosensis Pešić & Smit, 2015 is synonymized with Arrenurus flavus Smit, 2012. The first description of the female of Sterkspruitia comorosensis Pešić & Smit, 2015 is given. The number of water mites known from Comoros now tallies 17 species in ten families.